ANALISIS KUAT TEKAN BETON MENGGUNAKAN LIMBAH KERAMIK SEBAGAI PENGGANTI SEBAGIAN AGREGAT KASAR - Lydia Darmiyanti; Indriasari; Samrah Hawati Tambunan (Jurnal Sipil Krisna, 2022)
n construction work, it is often found that unused building materials / materials are disposed of as waste.If the waste is disposed of carelessly, it can cause new problems in the environment. Ceramic shard waste is anexample of a ceramic factory or building construction work. If you can process it creatively, it will produce amore useful product. The purpose of this study was to analyze the comparison of the results of the compressivestrength of concrete in normal concrete and concrete using ceramic waste. The author conducted this researchby comparing the results of the Slump Test and the results of the compressive strength of normal quality fc 25concrete with fc 25 concrete which has been added with ceramic waste as much as 20% and 40%. The test objectused in this study is a cylinder with a size of Ø15 cm x 30 cm, for each experiment as many as 6 specimens, witha compressive strength test carried out at the age of 7,14,28 days after first curring. From the results of this study,the slump value of fc 25 Normal Concrete and fc 25 Concrete with added ceramic waste material meets thestandard of slump target 7.5 cm to 15 cm, for plates, beams, columns and walls according to SNI 03-2834- 1992),and from the results of the compressive strength of fc 25 concrete with the use of ceramic waste by 20%, thecompressive strength of concrete is 21.36 MPa and the use of ceramic waste is 40%, the compressive strength ofconcrete is 17.68 MPa which is smaller than the compressive strength. Normal concrete fc 25 is 27.19 Mpa. Fromthe results of the concrete compressive strength, it can be seen that there is a decrease in the compressive strengthof the concrete due to an increase in the percentage of ceramic waste. So that it can be concluded that the use ofceramic shard waste composition is not recommended for building construction structures